Establishing a community advisory board to align harm reduction research with the unique needs of Black and Latine communities - Simon Kapler; Hira Hassan; Alexander Jeremiah; Katurah Bryant; Presto Crespo; Nesta Felix; Sónyi Elena Lopez; Antonio Morales; Sean Reeves; Ayana Jordan (Harm Reduction Journal)
Abstract Death from opioid use is a growing public health concern, with stark racial and ethnic disparities. The randomized controlled trial described here aims to improve initiation and engagement in harm reduction services for Black and Latine people who use drugs to minimize mortality in these populations. The trial is informed by a Community Advisory Board (CAB) of stakeholders from racial and ethnic minoritized backgrounds committed to promoting health equity in populations disproportionately impacted by the drug overdose crisis. CABs are an underutilized mechanism for engaging communities in research to improve health outcomes. Hence, in this manuscript we outline the process and methods employed in creating a CAB, describe its impact on our research study, and recognize the challenges and adaptations made to the CAB during the study. CAB recruitment targeted active community members from Black and Latine communities in the Bronx, NY and New Haven, CT. After attending community organizational meetings in each place, follow-up email efforts were unsuccessful, prompting a revised approach. Emphasizing the study’s focus on historically excluded voices, “research-naïve” individuals were sought through online searches and local grassroots organizations, excluding those affiliated with harm reduction groups to minimize bias. Once CAB members were identified, a remote orientation was held, and the CAB began providing regular feedback on research activities, from participant recruitment to educational script details. CAB members’ diverse identities and life experiences generated nuanced discussions, which were distilled into feedback improving research materials and recruitment strategies. In the future, the CAB will also guide data analysis and research publications. Other areas of emphasis have included straightforward language in study materials, balanced messaging about harm reduction recommendations, and specific community outreach opportunities. Practical barriers that needed to be addressed for optimal CAB functioning included timely compensation with minimal institutional burden and assistance with meeting coordination and communication. The CAB has ensured that Black and Latine community voices are included in guiding our study, promoting equitable and ethical research. As harm reduction research advances, it is essential to center this work around the intersectional identities of people who use drugs to prevent the disproportionate burden and deaths among Black and Latine people.